Luís Possolo: La stazione radio navale di Luanda e Angola - Saldanha, J. L. P. de (Africa big change, big chance, 2014)
Luis Gonzaga Pimentel Pedroso Possolo was born in Lisbon on July 7th. 1924. He graduated in architecture from the Lisbon Fine Arts Faculty in 1951 and later attended the inaugural 1954/55 edition of the Architectural Association Course of Training in Tropical Architecture, under the proposal of the Portuguese Gabinete de Urbanização do Ultramar, GUU (Overseas Planning Office) and approval of the Portuguese Overseas Affairs Undersecretary of State.